Engagement with Retirement Savings: It Is a Matter of Trust. Issue 3 (29th June 2018) - Deetlefs, A. M. Jeanette; Bateman, Hazel; Dobrescu, Loretti I.; Newell, Ben R.; Ortmann, Andreas; Thorp, Susan
Abstract : People who engage with their retirement savings are more likely to opt out of unsuitable defaults. We use cluster analysis of matched survey and administrative data to identify groups of pension plan members that are alike in their attitudes toward retirement saving. We find that engaged and disengaged members segregate into groups based on their interest and trust. Group membership in turn helps predict plan engagement, as proxied by nondefault choices. Specifically, engagement is stronger among interested groups. Trust, however, has a more complex relationship with engagement, particularly as it interacts with interest. While members with low interest and high trust are less likely to engage (e.g., by not checking plan performance), less trusting members engage more (e.g., by actively choosing asset allocations). As interest and trust successfully determine group membership, and ultimately engagement, pension plan providers should address members' diverse needs and circumstances with personalized approaches.